Genre et pratiques numériques selon l’origine sociale et le territoire, à l’entrée dans l’adolescence - Rozenn Décret-Rouillard (Éducation et Socialisation)
Our article examines 13 years-old adolescents’ practices of digital social networks and video games. The research, which is part of an intersectional model, questions gendered adolescent practices in the digital age, by confronting them with the social origin and the area of education of the surveyed. The results are based on a both quantitative (2475 students) and qualitative (180 students) survey carried out in the Rennes regional education authority. While our work confirms the determining role of gender in the differentiation of adolescent digital practices, it qualifies the exclusivity of the gender variable in the explanation of these practices among girls. Girls' digital practices are socially and, to a lesser extent, territorially differentiated. The gendered numerical intermingling of boys is much less subject to the effects of the parents' social category.